A New Technique to Quantitatively Determine the Periclase Content in High Magnesia Portland Cement - Ma, Zhongcheng; Yao, Yan; Liu, Zhicheng; Wei, Liying; Wu, Biao; Wen, Zhaijun; Lu, Chao (Frontiers in Materials, 2020)
An accurate quantification of periclase in high magnesia Portland cement (HMPC) is vital to evaluate the expansive property of this cement at a later age in practice. However, the existing methods to achieve this quantification are either limited in number or produce inaccurate results. In this study, a new Technique to quantitatively determine the content of periclase in HMPC was demonstrated by combining an autoclave test, a thermogravimetric analysis (TGA), and a chemical analysis; this was achieved by using the periclase standard substance (PSS) as the internal standard. The accuracy of this Technique was evaluated with regard to the recovery rate. Herein, an analytical grade reagent such as magnesium carbonate basic (Mg(OH)2·3MgCO3·3H2O) or magnesium hydroxide (Mg(OH)2) calcined at 1400 ℃ is recommended to be the PSS. The autoclave pressure should be 2.2 MPa, and the autoclave time should be 4 h. This novel Technique can avoid the interference of fused MgO in cement, and eliminate the influence of Mg(OH)2 and Ca(OH)2 (induced by the partial overlapping of their decomposition temperatures during TGA) on the periclase content. The results show that the recovery of PSS is between 99.92% and 100.14%, indicating that the Technique presents a good recovery effect and a relatively high accuracy. Therefore, this new Technique can be used to evaluate the expansive properties of HMPC and serve as a guidance for using HMPC in different practical applications according to the demand of a project.